EEG requests in paediatrics: an audit. Issue 6 (June 1995) - Nicolaides, P; Appleton, R E; Beirne, M
Abstract : An audit of 165 requests for electroencephalography (EEG) was undertaken before and after the introduction of guidelines and recommendations, 12 months apart. Inadequate clinical information was provided in requests in both surveys; 40% of requests were considered to be unnecessary, and approximately 50% of clinicians felt that EEG could diagnose epilepsy.